Teaching values through stories with morals (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article is an attempt to illustrate how the English language teacher can use stories of  English or American writers to inculcate high moral values, broaden student’s mind and alleviate prejudices.
Keywords: inculcation of values; value-based text; literary works; integrity